Memory and memorials, 1789-1914 : literary and cultural perspectives - Campbell, Matthew (Matthew J. B.); Labbe, Jacqueline M., 1965-; Shuttleworth, Sally, 1952- (Routledge studies in memory and narrative, 2000)
This volume explores the cultural importance of concepts and theories of memory. Ranging historically from the French Revolution to the beginnings of Modernism, it examines the importance of memory in cultural history.